Konsep Al-Birr dalam Tafsir Fi Zilal Al-Qur’an - Ahmad Bahrisy (CV. Syntax Corporation Indonesia, 2021)
This paper will discuss the issue of textual and contextual concepts of al-birr in the Qur'an according to Sayyid Qutb in tafseer fi Zilal al-Qur'an. After that it will be explained in detail the differences in the model of goodness based on the mufassir, and express the modern opinion of Sayyid Qutb contained in his interpretation. Sayyid Qutb classifies al-birr into 3 virtues, namely religion, social and character. Each verse containing lafad al-birr has different models of goodness and methods. The results of this study include: first, Sayyid Qutb explains that goodness is the instinct that every human being has. understanding al-birr is to be obedience, piety, kindness, compassion, truth, things do a lot of good, generosity, heaven, heart, accept, acceptable. Second, Sayyid Qutb initiates that goodness (al-birr) has 3 dimensions, namely the dimension of religion, social dimension and character dimension. The dimension of religion can be good when man's relationship to his Lord is good, with all the worship he does. The social dimension can be good when its relationship with humans, animals and other beings gets along well, respecting each other and understanding. The dimension of character can be good when one always trains oneself to put others above their own interests and direct their passions in a good direction.